Characteristics of strength and structure of PE - HD composite with addition of PE – HD waste - Dominik Grzesiczak,; Przemysław Postawa, (ACTA INNOVATIONS, 2016)
This article presents the possibilities of using the waste material obtained from the vehicle fuel tank (high density polyethylene PE- HD) as an addition to products. The waste material is added to the original polymer in an amount of 10% , 20% and 30%. The following tests have been performed during the research: differential scanning calorimetry DSC, static tensile test, hardness degree determined by pressing a steel ball, and also optical microscopy of obtained breakthroughs in samples made of liquid nitrogen. In addition, there has also been performed an analysis of mixture of original polyethylene that contains 10%, 20 % and 30 % of HD - PE polymer, which has been turned back for recycling from the production line. The aim of the research is to determine the recycling possibilities of polymeric materials obtained from the waste that emerged on the production line and in the fuel tanks of vehicles which were withdrawn from use as materials that during the utilization process have been subjected to a long-term connection with petroleum. Description of the mechanical and structural properties is an attempt to answer the question concerning usefulness of polymeric materials after utilization.